Balance Training in Pulmonary Rehabilitation. Issue 4 (July 2015) - Mkacher, Wajdi; Mekki, Marwa; Chaieb, Faten; Tabka, Zouhair; Trabelsi, Yassine
<x xml:space="preserve">Abstract</x> PURPOSE: Balance impairment in chronic obstructive pulmonary disease (COPD) is associated with a worsening of quality of life (QOL) as related with fatigue perception, depression, and anxiety. The aim of this study was to examine the effect of balance training included in pulmonary rehabilitation (PR) on QOL, fatigue perception, depression, and anxiety in patients with COPD. METHODS: Patients were assigned randomly to an intervention or PR-only group. The intervention group underwent balance training 3 times a week for 6 months concurrently with PR. The PR-only group received 6 months of the standard PR program. Quality of life was assessed at the beginning and at the end of the program using the St. George's Respiratory Questionnaire, fatigue using the Multidimensional Fatigue Inventory, and anxiety and depression using the Hospital Anxiety and Depression Scale. Exercise tolerance was determined from the 6-minute walk test. RESULTS: After the 6 months of the intervention or PR-only, both the intervention (n = 32) and PR-only (n = 30) groups improved their QOL (activity, impact, and total) with a significant intergroup difference (P < .05) after PR. General fatigue, physical fatigue, and reduced activity decreased in both groups with an intergroup difference (P < .05). Anxiety decreased significantly in both groups with a greater change in the intervention group (P < .01). Only the intervention group had an improved depression score at the end of 6 months. CONCLUSIONS: Balance training added to PR improved health-related QOL, fatigue, and mental health in patients with COPD.